The Effect of Social and Personality Factor on Attitude Toward Brand and Purchase Intention - Budiman, Santi - (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
The purpose of this research was to examine the influence of social and personality factor on attitude toward brand and purchase intentions. It was carried out because currently, the purchase of branded bags overgrows in Indonesia. In this research, sampling employed non-probability with the purposive sampling technique. The data collection technique in this research used a questionnaire distributed online according to predetermined criteria i.e., branded bag consumers who had purchased a minimum once in the last six months. This study's sample was buyers of branded bags in Indonesia, with as many as 150 respondents. The method utilized was Structural Equation Modeling (SEM). This study’s findings indicated that social and personality factor influenced consumer purchase intention. Social and personality factor influenced purchase intention mediated by attitude toward brand. In addition, the relationship between social factor and purchase intention was moderated by hedonic value. Likewise, personality factor and purchase intention were moderated by hedonic value.